Semiotic Study Of Traditional Wedding Clothes In Du Village - Siano, Felisitas; Ekhsan, Nur Syamsiyah; Naro, Antonius M.K. (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This study aims to identify and analyze the meanings contained in traditional wedding clothes and accessories used at community weddings in Du Village, Lela Subdistrict, Sikka District. This research is a qualitative research method. Data collection techniques used in this study were observation, interviews and documentation studies. The results of the researcher's analysis found that the traditional clothes and accessories worn at the wedding in Du Village had their own meaning. The researcher concludes that the overall meaning contained in the traditional wedding clothes and the accessories used is to uphold self-respect and human rights.